2017
DOI: 10.3390/ijms18102114
|View full text |Cite
|
Sign up to set email alerts
|

A Central Bioactive Region of LTBP-2 Stimulates the Expression of TGF-β1 in Fibroblasts via Akt and p38 Signalling Pathways

Abstract: Latent transforming growth factor-β-1 binding protein-2 (LTBP-2) belongs to the LTBP-fibrillin superfamily of extracellular proteins. Unlike other LTBPs, LTBP-2 does not covalently bind transforming growth factor-β1 (TGF-β1) but appears to be implicated in the regulation of TGF-β1 bioactivity, although the mechanisms are largely unknown. In experiments originally designed to study the displacement of latent TGF-β1 complexes from matrix storage, we found that the addition of exogenous LTBP-2 to cultured human M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…We also detected upregulation of Ltbp isoforms, Ltbp1 , Ltbp2 and Ltbp3 . Their modulation can be directly mediated by ROS production (Jobling et al 2006 ) and activate the p38 MAPK pathway (Sideek et al 2017 ) linked to gliosis (Kaminska et al 2009 ). Thus, we analyzed p38 MAPK signaling and found evidence of activation of the non-canonical p38 MAPK pathway—likely mediated by TGFβ1 and TGFβ2—during gliotic response in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected upregulation of Ltbp isoforms, Ltbp1 , Ltbp2 and Ltbp3 . Their modulation can be directly mediated by ROS production (Jobling et al 2006 ) and activate the p38 MAPK pathway (Sideek et al 2017 ) linked to gliosis (Kaminska et al 2009 ). Thus, we analyzed p38 MAPK signaling and found evidence of activation of the non-canonical p38 MAPK pathway—likely mediated by TGFβ1 and TGFβ2—during gliotic response in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study has revealed that LTBP2 competes with LTBP1 by binding to fibrillin-1, suggesting an indirect role of LTBP2 in the storage and activation of TGF-β, a major profibrotic growth factor [34]. In addition, Sideek et al [35] recently reported that a bioactive region of LTBP2 can directly up-regulate TGF-β1 expression. On the other hand, previous studies suggested the antifibrotic role of LTBP2 via inhibition of fibroblast growth factor-2-induced fibroblast proliferation and fibroblast adhesion to fibronectin [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs secreted several proteins solely following traumatic stimulus, potentially participating in damage repair. Latent transforming growth factor-β1 binding protein 2 (LTBP-2, Table 1) has been reported to stimulate the expression of TGF-β1 in fibroblasts [48]. In the IVD, TGF-β1 has been associated with alleviation of the inflammatory response, inhibition of ECM degradation, Table 1 Proteins identified in secretomes of mesenchymal stromal cells stimulated with healthy, traumatic, or degenerative intervertebral disc conditioned medium or IL1-β, with a log2 fold-change > 1.5 (relative to the baseline control stimulation) (Continued) inhibition of cell death, increased ECM synthesis, and promotion of cell proliferation [49].…”
Section: Discussionmentioning
confidence: 99%